PENGARUH PENGAWASAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI KANTOR CAMAT MENYUKE KABUPATEN LANDAK - Socha Summarjaya E.42008090 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
The title of this research is the "Influence of the Controlling on Work Productivity of Menyuke District office staff of Landak Regency”. This research purpose to find out and analyze: 1) Work Productivity of Menyuke District office staff of Landak Regency; 2) Controlling of Menyuke District office staff of Landak Regency; 3) Influence of the Controlling on Work Productivity of Menyuke District office staff of Landak Regency. This research was chosen because the author viewed the existence of phenomena that lead to decreased employee productivity. The author has presumption that an effective controlling will improve the productivity of work staff. This research including the type of quantitative research with hypothesis testing. The population in this study amounted to 11 people. Data collection techniques using questionnaire which has been tested in advance and tested the validity and reliability. Analysis techniques used are Simple Linear Regression. The results showed a correlation of 0,710 meaning significance of the strong correlation coefficient on the interval 0.526-0,799 and rarithmetic > rtable (0,666 > 0,710), so then the hypothesis proposed is accepted. Test results the coefficient of determination R2 values obtained by = 0,504 which indicates that a variable Controlling effect on work productivity of 50,4%. is means that effective control has a link in improving work productivity. The remaining 49.6% are affected by other variables which are not examined, such as discipline, motivation, work environment and others.Keywords: Controlling, Work Productivity.